STUDY ON FACTORS AFFECTING INVESTOR BEHAVIOUR IN FINANCIAL MARKETS WITH SPECIFIC REFERENCE TO MUMBAI - et. al., CA. Jai Kotecha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research paper is to analyse the factors affecting Investor behaviour in Financial markets. The purpose of study is to find out the factors influencing investor behaviour decisions pertaining to investment in financial markets. Earlier the investment pattern was only bank deposits, bonds, schemes etc but nowadays it has evolved into alternate investment. Alternative investments consist of Hedge funds, Private equity funds, financial markets etc. For this study we have collected primary data from respondents through a specific formed questionnaire. The data has been analysed through ANOVA test.